MANAJEMEN PENDIDIKAN SEKOLAH INKLUSI UNTUK MENINGKATKAN MUTU HASIL BELAJAR ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR TAMANSISWA IBU PAWIYATAN YOGYAKARTA TAHUN AJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
The objective of the research are to describe inclusion education management to increase the learning output quality of children with special needs which includes planning, application, evaluation, obstacles, and effort to overcome the obstacles of inclusion education management to increase the learning output quality of children at Tamansiswa Ibu Pawiyatan Elementary School, Yogyakarta.This reaserach is a qualitative-descriptive research. It is conducted at Tamansiswa Ibu Pawiyatan Elementary School, Yogyakarta. The data resources of this research were headmaster, teachers, teacher's assistants, school's treasurers, and school's supporting facilities. Data collection technique used in this research were interview, observation, and documentation. The research findings was analysed and reported in meaningful qualitative words. The researcher acts as an instrument. The data validity test used data credibility test which covers validity, reliability, and objectivity. In addition to persistent observation, the researcher also used triangulation kredibility test. The technique to check data validity was triangulation method to test credibility.The research findings show that 1) the planning applied in Tamansiswa Ibu Pawiyatan Elementary School does not work to its maximum effect since the school is still using original KTSP 2) the application of learning activity works quite well, the teachers' lack of knowlwdge in inclusion education 3) the evaluation of inclusion education application do it 4) the obstacles curriculum was still the original KTSP, the of lack facilities and infrasructure provided by the school, financial management which does not give authority to the school to self-manage itself; 5) the effort done by the school to overcome the obstacles in curriculum planning was to implement modified curriculum.